Perbedaan Aspirasi Karier Siswa ditinjau dari Jenis Kelamin, Jurusan, dan Tingkat Pendidikan Orangtua serta Implikasinya terhadap Pelayanan Bimbingan dan Konseling - Febriani, Rahmi Dwi; Yusuf, A. Muri; Iswari, Mega (Konselor, 2016)
Career aspiration is an important for students, because needs to be done first when choosing one career is to have career aspiration. The fact in the field signified that the students do not have a career goal in the future. This is an indication that the students career aspiration are in the low category. The aim of this research was to: (1) describe students career aspiration is sighted of sex, majors, and parents educational level, (2) examined differences in students career aspiration of male and female, (3) examined differences in career aspiration of students majoring in science and social studies, (4) examined differences in students career aspiration is sighted of parents educational level, and (5) examined differences in students career aspiration is sighted of interaction of sex, majors, and parents educational level. The research methods applied in this research was ex post facto with factorial design 2 x 3 x 2. The population this research was consisted of 837 students in SMAN 7 Padang. The number of samples as much as 270 students were selected by propotional random sampling technique. The instrument of the research was career aspiration scale with reliability 0.885. Data were analyzed using descriptive statistics and analysis of variance. The result of the research indicated that: (1) In general, career aspiration of studentsÂ  is sighted of sex, majors, and parents educational level were in high category, (2) there is no significant differences between career aspiration of male and female students, (3) there is no significant difference between career aspiration of students majoring in science and social studies, (4) there was a significant difference between career aspiration of students having parents educational level of high, medium, and low, (5) there is no significant differences in students career aspiration is sighted of interaction of sex, majors, and parents educational level.Â